2018
DOI: 10.1021/acs.jproteome.8b00062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasmodium falciparum Atypical Kinase PfPK7 Dependent Phosphoproteome

Abstract: PfPK7 is an "orphan" kinase displaying regions of homology to multiple protein kinase families. PfPK7 functions in regulating parasite proliferation/development as evident from the phenotype analysis of knockout parasites. Despite this regulatory role, the functions of PfPK7 in signaling pathways are not known. To better understand PfPK7-regulated phosphorylation events, we performed isobaric tag-based quantitative comparative phosphoproteomics of the schizont and segmenter stages from wild-type and pfpk7 para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…To test the accuracy of the p-values reported by motif-x * , we examined whether they follow the expected uniform distribution when the input peptides are random. We sorted together p-values of all the motifs reported by motif-x * when run with 10,000 shuffled versions of the Pease et al [15] Supplemental Data 2 dataset, and we plotted the reported p-value as a function of its rank in the sorted list ( Fig. 1).…”
Section: Testing Methodology and Datamentioning
confidence: 99%
See 4 more Smart Citations
“…To test the accuracy of the p-values reported by motif-x * , we examined whether they follow the expected uniform distribution when the input peptides are random. We sorted together p-values of all the motifs reported by motif-x * when run with 10,000 shuffled versions of the Pease et al [15] Supplemental Data 2 dataset, and we plotted the reported p-value as a function of its rank in the sorted list ( Fig. 1).…”
Section: Testing Methodology and Datamentioning
confidence: 99%
“…First, we reproduced the motif-x results from Fig. 3C in Pease et al [15]. Running motif-x * with the same input files (the 196 sequences from Pease et al…”
Section: Momo's Enhanced Version Of Motif-x Accurately Reproduces Thementioning
confidence: 99%
See 3 more Smart Citations